ANALISIS REALISASI PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) DAN BIAYA BALIK NAMA KENDARAAN BERMOTOR (BBNKB) PADA SAMSAT INDUK SAMARINDA - -, Dwi Rossiyanti (EKONOMIA, 2019)
Taxes in essence not only function as a source of state finance (Budgetfair) butalso have a broader function which means that the tax can be used as a tool to regulate and implement state policies in the economic and social fields. Nevertheless the main tax function is the source of state finance because in the budget and state revenues most of it is influenced and fulfilled from the tax sector, namely motor vehicle tax and the cost of returning the name of the motor vehicle. The purpose of this study is: to determine the level of effectiveness Motorized Vehicle Tax for 2012-2016 at Samarinda Parent Samsat, and to determine the level of effectiveness of Motor Vehicle Transfer Fee for 2012-2016 at Samarinda Parent Samsat. Knowing whether the level of effectiveness has decreased or increased from the data obtained in Samarinda Parent Samsat with research from 2012 to 2016. The research data uses the effectiveness level analysis method. Based on the results of data analysis using the effectiveness method, the PKB results in 2012 reached 99.74% and BBNKB 106%, in 2013 it reached PKB 108.70% and BBNKB 90.65%, then in 2014 PKB reached 105.86% and BBNKB 88.94%, in 2015 reached 103.69% PKB and 90.21% BBKB and 98.74% BBNKB and 104.90% BBNKB. The results of the hypothesis were rejected because the 2012-2016 CLA was said to be effective while the BBNKB results in 2012 to 2016 the results of the hypothesis were accepted because in 2014 BBNKB was said to be less effective.